2010
DOI: 10.2460/ajvr.71.9.1100
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate in dogs as estimated via plasma clearance of inulin and iohexol and use of limited-sample methods

Abstract: Use of iohexol and inulin yielded similar but not identical results for plasma clearance. Accuracy for limited-sample methods would be acceptable for many clinical and research situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Recognizing that inulin clearance is the gold standard methodology for GFR measurement, iohexol clearance is a validated and widely performed method of assessing GFR that is more practical to perform clinically. Although obtaining more blood samples to calculate GFR using a noncompartmental model may be more accurate, previous research has demonstrated limited sample methods of calculating GFR using iohexol clearance to be acceptable . Urine output was not measured in our study because of possible changes in GFR as a result of the sedation required for urethral catheterization.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recognizing that inulin clearance is the gold standard methodology for GFR measurement, iohexol clearance is a validated and widely performed method of assessing GFR that is more practical to perform clinically. Although obtaining more blood samples to calculate GFR using a noncompartmental model may be more accurate, previous research has demonstrated limited sample methods of calculating GFR using iohexol clearance to be acceptable . Urine output was not measured in our study because of possible changes in GFR as a result of the sedation required for urethral catheterization.…”
Section: Discussionmentioning
confidence: 98%
“…Although obtaining more blood samples to calculate GFR using a noncompartmental model may be more accurate, previous research has demonstrated limited sample methods of calculating GFR using iohexol clearance to be acceptable. 25 Urine output was not measured in our study because of possible changes in GFR as a result of the sedation required for urethral catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma iohexol concentration was determined via high-performance liquid chromatography 17 at the Norwegian School of Veterinary Science. Plasma standard solutions (1, 10, 50, 100, and 250 µg of iohexol/mL) were made by diluting the iohexol stock solution (647 g/L, which corresponded to 300 g of iodine/L) with pooled plasma obtained from 10 healthy dogs from which food had been withheld.…”
Section: Assay Of Creatinine and Iohexol Concentrations-mentioning
confidence: 99%
“…In addition, PECC and PIoxC have the practical advantages of being plasma clearance methods that have been validated separately against criterion-standard methods (eg, inulin or creatinine clearance). 4,17 However, to our knowledge, they have not been compared in a large field population of dogs to determine whether PECC and PIoxC can be used interchangeably or whether there is an advantage for one over the other when screening a population of potentially diseased dogs. Discrepancies between the 2 methods could be problematic for screening of patients and when conducting research in canine nephrology.…”
mentioning
confidence: 99%
“…The Henle's loop penetrates toward the renal pelvis where it turns 180° and comes back to the cortex as a straight distal tubule. In the cortex, a straight distal tubule coils into a distal convoluted tubule and opens into a collecting tubule of medullary rays which collect urine and finally drain into the renal pelvis [2][3][4].…”
Section: Introductionmentioning
confidence: 99%